2012
DOI: 10.3928/15428877-20121001-02
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness Measurement in Highly Myopic Eyes Using SD-OCT

Abstract: In highly myopic eyes, the choroid is thin and undergoes further attenuation with age and increasing myopia. In addition, these findings suggest that the choroid may play a role in the pathogenesis of CNV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…As an example, in Vogt-Koyanagi-Harada disease choroidal thickness is reduced after succesful steroid treatment; therefore, can be an important indicator for the assessment of corticosteroid treatment efficacy [16]. Recent studies also showed a decrease in choroidal thickness in highly myopic eyes [27,28] which is supposed to be a significant risk for the developement of choroidal neovascularisation. Other recently published data showed that macular choroidal thickness is not influenced by intraocular pressure [29].…”
Section: Discussionmentioning
confidence: 99%
“…As an example, in Vogt-Koyanagi-Harada disease choroidal thickness is reduced after succesful steroid treatment; therefore, can be an important indicator for the assessment of corticosteroid treatment efficacy [16]. Recent studies also showed a decrease in choroidal thickness in highly myopic eyes [27,28] which is supposed to be a significant risk for the developement of choroidal neovascularisation. Other recently published data showed that macular choroidal thickness is not influenced by intraocular pressure [29].…”
Section: Discussionmentioning
confidence: 99%
“…For each location, the average of the two readers’ measurements was used or the consensus value, if necessary. Consensus grading occurred if the two readers’ choroidal thickness differed by either 15% 23-24 or 30 μm. This method of manual choroidal thickness measurement using digital calipers has been shown to be highly repeatable.…”
Section: Methodsmentioning
confidence: 99%
“…6 A significant thinning in CT related with myopia was observed and CT in myopia had negative correlation with refractive power, axial length, and age, which was mentioned in previous studies (Table 3). 5,6,16,18,19 Excimer laser refractive surgery is a common option for correcting myopia. Our study, first reported that the choroid becomes thicker following myopic refractive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 In profoundly affected myopic eyes, the choroid is thinner than in normal eyes, and it undergoes further thinning with age and increasing myopia. 5,6 A thinner choroid could be instrumental in the onset and progression of severe myopia-related diseases. 7 Increasing numbers of ophthalmic scholars and clinicians are focusing on choroidopathy induced by myopia.…”
Section: Introductionmentioning
confidence: 99%